2014
DOI: 10.1002/jsfa.6554
|View full text |Cite
|
Sign up to set email alerts
|

Thermal resistance ofSalmonella enterica, Escherichia coliandStaphylococcus aureusisolated from vegetable feed ingredients

Abstract: These results provide relevant information for improvement in the safety of cattle feed regarding its process conditions (i.e. time, temperature and particle size).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…For incubation temperatures of 35 and 45°C, both decrement and increment of pH from 7.4 to 6.0 and from 7.4 to 9.0, respectively, shortened D ‐values , indicating that decimal reduction time of the bacteria was the longest at pH 7.4. In a similar thermal tolerance study on Salmonella enterica grown at 37°C and pH 7, Amado, Vázquez, Guerra, and Pastrana () reported D ‐values of 0.44–1.35 min at 60°C and 0.22–0.66 min at 65°C, which agree well with the results found in our study (1.1–1.2 min at 60°C and 0.3 min at 65°C) on Salmonella grown at 35°C.…”
Section: Resultssupporting
confidence: 91%
“…For incubation temperatures of 35 and 45°C, both decrement and increment of pH from 7.4 to 6.0 and from 7.4 to 9.0, respectively, shortened D ‐values , indicating that decimal reduction time of the bacteria was the longest at pH 7.4. In a similar thermal tolerance study on Salmonella enterica grown at 37°C and pH 7, Amado, Vázquez, Guerra, and Pastrana () reported D ‐values of 0.44–1.35 min at 60°C and 0.22–0.66 min at 65°C, which agree well with the results found in our study (1.1–1.2 min at 60°C and 0.3 min at 65°C) on Salmonella grown at 35°C.…”
Section: Resultssupporting
confidence: 91%
“…The inactivation curves exhibited slightly upward concavity with tailing (Figures 2 to 4). Amado et al. (2014) observed that the thermal resistance of S. aureus isolated from vegetable feed ingredients mostly exhibited tailing, which, according to the authors, indicated the presence of a highly heat-resistant subpopulation.…”
Section: Resultsmentioning
confidence: 97%
“…(2014) observed that the thermal resistance of S. aureus isolated from vegetable feed ingredients mostly exhibited tailing, which, according to the authors, indicated the presence of a highly heat-resistant subpopulation. Kamau’s model was found to be suitable for describing the thermal resistance of S. aureus (Amado et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the food product must be packaged under sterile conditions (Barrett and Lloyd, 2012). However, an increase in the thermal resistance of microorganisms due to adverse environmental conditions has been reported (Amado et al, 2014) as well as the loss of both sensorial and nutritional characteristics (Barba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%